Material matters: artificial substrate composition and biofilm presence influence larval settlement of Diadema antillarum - Rippen, Johanna Catharina; Wijers, Tom; Van Bruggen, Charlotte Geerte Elisabeth; Antoun, Marc; Eriksson, Britas Klemens; Hylkema, Alwin (Frontiers in Marine Science, 2025)
Caribbean coral reefs are in rapid decline and artificial reefs are increasingly often deployed to restore lost three-dimensional structure. The majority of artificial reefs and other marine infrastructure is built from concrete, with Ordinary Portland Cement (CEM I) as the most important ingredient. However, the production of CEM I results in substantial CO2 emissions. In addition, there are indications that the material is colonized by different benthic assemblages compared to natural reefs. To make artificial reefs more sustainable and ecologically optimal, research into alternative materials is required. For this study, CEM I was compared with five alternative substrates: a mixture of CEM III cement with recycled CEM I fines (CEM III), Calcium Sulfoaluminate cement (CSA), geopolymer-sediment tiles (GS), lime-sediment tiles (LS), and Xiriton (E0). Settlement of the long-spined sea urchin Diadema antillarum on the different materials was tested under marine laboratory conditions. Competent D. antillarum larvae were added to beakers with a tile made from one of the substrates and monitored for settlement after two days. Half of the tiles of each material were covered with a four-week old biofilm, the other half had no biofilm. Results show that substrate type and the presence of a biofilm affected settlement rates significantly. After 48h, highest settlement rates were found on CEM III with biofilm (30% settlement), CSA with biofilm (26% settlement) and E0 with biofilm (20% settlement). Without biofilm, the same substrates yielded only 4 to 10% settlement. CEM I, GS, and LS had overall low settlement rates (<5%) irrespective of biofilm. Post-settlement morphology was not affected by substrate type or biofilm, with juveniles having a mean test diameter of 593 ± 12 µm and a mean spine length of 487 ± 27 µm. This study provides alternative choices for regular concrete that enhance the larval settlement of the key herbivore D. antillarum. We recommend studying these alternative materials in the field to obtain a better understanding of the effects of substrate on the ecological community development over larger time- and spatial scales.